2012
DOI: 10.1111/j.1471-3802.2012.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Botswana primary schools teachers' perception of inclusion of learners with special educational needs

Abstract: The purpose of this study is to investigate the perception of primary teachers towards inclusive education in the South Central regions of Botswana. The research employed a descriptive survey design that used both qualitative and quantitative research methodology. Two hundred and seventy-three primary teachers were drawn from a sample size of 2950 teachers and 165 schools. Multistage proportionate stratified sampling was utilised to select teachers from these three different locations: urban, semi-urban and ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 11 publications
(18 reference statements)
1
19
0
13
Order By: Relevance
“…The primary and the most important stage in the preparation of the education system to the implementation of the process of inclusion is the stage of psychological and value changes as well as changes of professional competence of specialists (Mukhopadhyay (2014)). …”
Section: Resultsmentioning
confidence: 99%
“…The primary and the most important stage in the preparation of the education system to the implementation of the process of inclusion is the stage of psychological and value changes as well as changes of professional competence of specialists (Mukhopadhyay (2014)). …”
Section: Resultsmentioning
confidence: 99%
“…Of those studies, some reported that teachers hold positive attitudes towards inclusion of children with special needs (Avramidis, Bayliss, and Burden 2000;Hadjikakou and Mnasonos 2012;Park and Chitiyo 2011;Sakiz and Woods 2014;Sari 2007;Sucuoglu 2004), while some others showed that teachers possess negative (Alquraini 2012;Block and Obrusnikova 2007;Gok and ErbaS 2011;Martin, Johnson, Ireland, and Claxton 2003;Mukhopadhyay 2014;Rakap and Kaczmarek 2010;Sadioglu et al 2013;Secer 2010;Semmel et al 1991) or neutral attitudes (Engstrand and Roll-Pettersson 2012;Leyser and Tappendorf 2001;Ross-Hill 2009;Sari, Celikoz, and Secer 2009) towards inclusion of children with disabilities. In their review of the literature, Avramidis and Norwich (2002) identified several factors that influence teachers' attitudes towards inclusion/integration.…”
Section: Literature On In-service and Pre-service Teacher Attitudes Tmentioning
confidence: 99%
“…As the number of students with exceptionalities attending local schools continues to increase-due to integrated and inclusive ministry and school policies-classrooms will become increasingly diverse, challenging educators to re-evaluate their perceptions and ideals and adjust their pedagogy (Berry, 2011;Mukhopadhyay, 2014). A significant body of research indicates that globally, teachers' positive attitudes towards the inclusion of students with exceptionalities are critical to successfully create an inclusive classroom.…”
Section: Teacher Attitudes Regarding Inclusionmentioning
confidence: 99%
“…Positive attitude declining as years of teaching experience increases has also been supported in other literature (Alghazo & Naggar Gaad , 2004;Glaubman & Lifshitz , 2001). Mukhopadhyay's (2014) framework for stages of professional development for educators categorizes educators based on their beliefs about professional development and changing practice. Teachers who were at the stages of professional development of either Competency Building or of Enthusiasm and Growth (beginning half of their careers) were more willing to engage in pedagogical change when compared to those in the last half of their career, especially in the years before retirement (Boer et al, 2011;Mukhopadhyay, 2014).…”
Section: Teacher Attitudes Regarding Inclusionmentioning
confidence: 99%
See 1 more Smart Citation